Hubungan antara Karakteristik Demografi, pengetahuan Pengobatan Tradisional, dan Jenis Penyakit Pasien denganPemilihan Pengobatan Tradisional Nakamura di Surakarta - MARDIONO, ANGGI (2011)
Non-conventional medication whose utilization is very high in the society is traditional and alternative medication, including Nakamura. Nakamura is a traditional medication from Japan which consists of three techniques, namely reflection, acupressure, and cyropract. This research aimed to understand the relationship between demographic characteristics, knowledge of traditional medication, and kinds of patients' disease with traditional medication option Nakamura in Surakarta. The type of this research was observational with case control study as research draft. Sampling on this research was people who chose traditional medication Nakamura with the total of 192 respondents which consisted of 96 respondents for case group and 96 respondents for control group. The used sampling for case group was quota sampling and purposive sampling for control group. The used statistic test for analyzing the data of this research was chi square test. The research result showed that there was significant result between demographic characteristics which was the result (p = 0.008; OR = 2.340; CI 95% = 1.242-4.409) and knowledge (p = 0.000; OR = 7.600; CI 95% = 3.967-14.560) with the option of traditional medication. Then there was no significant relationship between education as demographic characteristics (p =0.156; OR = 1.991; CI 95% = 0.758-5.234), job (p = 0.848; OR = 0.929; CI 95% = 0.439-1.968), physical disease (p = 0.131; OR = 1.669; CI 95% = 0.856- 3.253), and psychological disease (p = 0.385; OR = 0.777; CI 95% = 0.440-1.373) with the option of traditional medication Nakamura.